Baseline level and change trajectory of the triglyceride-glucose index in relation to the development of NAFLD: a large population-based cohort study - Wang, Yaqin; Wang, Jiangang; Liu, Lei; Yang, Pingting; Deng, Shuwen; Liu, Xuelian; Zhao, Linlin; Wang, Changfa; Li, Ying (Frontiers in Endocrinology, 2023)
Background: Insulin resistance (IR) and nonalcoholic fatty liver disease (NAFLD) are closely related. The triglyceride-glucose index (TyG index) has been proposed as a new indicator of IR. It remains unclear whether the triglyceride-glucose (TyG) index is prospectively associated with incident nonalcoholic fatty liver disease (NAFLD). Methods: This large-scale study comprised 1 prospective cohort totaling 22,758 subjects without NAFLD at baseline who underwent repeated health examinations and 1 subcohort totaling 7,722 subjects with more than three visits. The TyG index was ascertained mathematically by ln (fasting triglycerides [mg/dL] × fasting glucose [mg/dL]/2). NAFLD was diagnosed by ultrasound without other concomitant liver diseases. A combinatorial Cox proportional hazard model and latent class growth mixture modeling method were used to identify the association of the TyG index and its transition trajectories with NAFLD risk. Results: During 53,481 person-years of follow-up, there were 5319 incident cases with NAFLD. Compared with those in the lowest quartile of the baseline TyG index, participants in the highest quartile had 2.52-fold (95% confidence interval, 2.21–2.86) higher odds of incident NAFLD. Similarly, restricted cubic spline analysis showed a dose–response relationship (p nonlinearity<0.001). Subgroup analyses showed a more significant association in the female and normal body size populations (p for interaction<0.001). Three distinct trajectories of changes in the TyG index were identified. Compared with the continued low group, the moderately increasing and highly increasing groups conferred 1.91-fold (1.65–2.21) and 2.19-fold (1.73–2.77) higher NAFLD risk, respectively. Conclusions: Participants with a higher baseline TyG index or a higher excessive TyG exposure were associated with an increased NAFLD risk. The findings imply that lifestyle interventions and modulation of IR might be considered to both reduce TyG index levels and prevent NAFLD development.